An Experimental Study of the Lingual Consciousness of Ukrainians and Russians (Dynamic Aspect) - Terekhova, Diana; Терехова, Діана (My University, 2018)
The study of the lingual consciousness of various ethnic group representatives does not lose its topicality in psycholinguistic investigation for decades. During the period of the formation and development of psycholinguistics, scientists have gained considerable experience in doing associative experiments, the results of which are reflected in associative dictionaries and individual scientific investigations. This material is valuable in several aspects of the investigation in particular as an object of the study of the lingual consciousness of the certain language speakers for the duration of the experiment; in the comparable aspect for the identification of common and distinguishing features in the lingual consciousness of the representatives of different ethnic groups as well as to find out the changes in the lingual consciousness of the representatives of a certain ethnic group according to the experimental data received at a certain time interval, etc. The article focuses on revealing the dynamics of the lingual consciousness of two East Slavic language speakers – Ukrainian and Russian. The material resulted from a series of experiments recorded in lexicographic psycholinguistic works and self-conducted studies held in 2000 and in 2012 representing the changes in the corresponding fragments of the world image of the Ukrainians and Russians. Вивчення мовної свідомості представників різних етносів не втрачає своєї актуальності у психолінгвістичних розвідках останніх десятиліть. За період становлення та розвитку психолінгвістики науковці накопичили значний досвід проведення асоціативних експериментів, результати яких відбито в асоціативних словниках та окремих наукових розвідках. Цей матеріал є цінним у кількох аспектах дослідження, зокрема як об’єкт вивчення мовної свідомості носіїв певної мови саме на період проведення експерименту, у зіставному аспекті для виявлення спільних та відмінних рис у мовній свідомості пред-ставників різних етносів, а також для з’ясування змін у мовній свідомості преставників певного етносу за експериментальними даними, отриманими на певному часовому про-міжку тощо. Отже статтю присвячено виявленню динаміки мовної свідомості представ-ників двох східнослов’янських народів. Матеріалом обрано результати експериментів, зафіксованих у лексикографічних психолінгвістичних працях, та власноруч проведених експериментальних досліджень 2000 та 2012 років, що репрезентує зміни у відповідних фрагментах образу світу українців та росіян.
Експериментальне дослідження мовної свідомості українців та росіян (динамічний аспект)
Keywords: world image; linguistic consciousness; associative experiment; association; associative field; associative gestalt; образ світу; мовна свідомість; асоціативний експеримент; асоціація; асоціативне поле; асоціативний гештальт